EKSPLORASI SUMBERDAYA AIR TANAH DI DAERAH HANDIL BABIRIK KABUPATEN TANAH LAUT - Prayogo, Teguh (Center for Environmental Technology, 2008)
Ground water is water located beneath the ground surface in soil pore spaces and in the fractures of lithologic formations. A unit of rock or an unconsolidated deposit is called an aquifer when it can yield a usable quantity of water. Ground water is alternative water to meet a demand of water supply, because the availability of surface water at an area is sometimes not enough to fulfill the need of drinking water, like occured in the Handil Babirik area. In this paper will be discribed concerning application of imaging resistivity technology for understanding characteristic and condition of ground water in Handil Babirik, Tanah Laut district, SouthKalimantanProvince. The result of survey in field, data processing, modelling and interpretation indicated that the existence of aquifer in Handil Babirik area is occupied between 30 Ã¢â‚¬â€œ 40 meter depth and having a form of lens.Ã‚Â Keywords : Handil Babirik, ground water, imaging resistivityÃ‚Â